Exemplifying a Model-Eliciting Task for Primary School Pupils - Chan Chun Ming Eric; Wanty Widjaja; Ng Kit Ee Dawn (Southeast Asian Mathematics Education Journal, 2011)
Mathematical modelling is a field that is gaining prominence recently in mathematics education research and has generated interests in schools as well. In Singapore, modelling and applications are included as process components inrevised 2007 curriculum document (MOE, 2007) as keeping to reform efforts. InIndonesia, efforts to place stronger emphasis on connecting school mathematicswith real-world contexts and applications have started in Indonesian primary schools with the Pendidikan Realistik Matematik Indonesia (PMRI) movement a decade ago (Sembiring, Hoogland, Dolk, 2010). Amidst others, modelling activities are gradually introduced in Singapore and Indonesian schools to demonstrate the relevance of school mathematics with real-world problems. However, in order for it to find a place in the mathematics classroom, there is aneed for teacher-practitioners to know what mathematical modelling and what amodelling task is. This paper sets out to exemplify a model-eliciting task that has been designed and used in both a Singapore and Indonesian mathematicsclassroom. Mathematical modelling, the features of a model-eliciting task, and its potential and advice on implementation are discussed.